Cara Meningkatkan Keterampilan Dan Produktivitas Pekerja Pada Kebun Sayur Central Hidroponik Bengkulu - Huda, Okta Nurul; Nasution, Suswati; Handayani, Sri; Hanila, Siti (Jurnal Dehasen Mengabdi, 2024)
Agriculture plays an important role in the Indonesian economy, with vegetable plantations being key in meeting people's food needs. The city of Bengkulu, with its geographical potential and favorable climate, offers great opportunities to improve the skills and productivity of vegetable farmers. However, challenges such as limited access to modern technology, lack of technical knowledge, as well as climate change and market dynamics hinder the development of this sector. This research aims to explore strategies to improve the skills and productivity of vegetable farmers in Bengkulu City through education, training, introduction of the latest technology, and development of marketing networks. With a participatory approach involving local farmers, agricultural extension workers and agronomists, the proposed solutions are expected to be relevant and applicable. The research results show that improving skills, applying modern technology and good agricultural practices can significantly increase farmers' productivity and welfare. The implementation of this solution is expected to have a positive impact on the local economy and the sustainability of the agricultural sector in Bengkulu City.